Quantum computing in cryptography: Exploring vulnerabilities and countermeasures - Kurniawan, Deni; Triyanto, Dedi; Wahyudi, Mochamad; Pujiastuti , Lise (Institute of Computer Science (IOCS), 2023)
This research delves into the critical analysis of vulnerabilities arising from the advent of quantum computing in traditional cryptographic systems. Employing a newly developed mathematical formulation model, the study meticulously evaluates the susceptibility of classical encryption methods, exemplified by XYZ Bank's RSA and ECC algorithms, to quantum algorithms such as Shor's and Grover's. The assessment reveals pronounced vulnerabilities, particularly highlighting the high susceptibility of RSA encryption to quantum attacks, emphasizing the urgent need to fortify existing cryptographic systems. The research rigorously evaluates potential countermeasures, with Post-Quantum Cryptography (PQC) emerging as a promising solution, showcasing superior effectiveness in mitigating vulnerabilities posed by quantum algorithms. The strategic imperative for organizations to transition towards PQC or other post-quantum cryptographic standards is evident, signaling a paradigm shift towards resilient encryption methods resilient to the disruptive capabilities of quantum computing. The research underscores the significance of collaboration among industry stakeholders, continuous research endeavors, and proactive measures in adopting quantum-resistant cryptographic standards to fortify data security strategies against potential quantum threats in an ever-evolving technological landscape.